Term limits and voter turnout - Veiga, Francisco José (2018)
This paper studies the impact of binding term limits on voter turnout, analyzing the Portuguese experience at the local government level, where the institutional reform was exogenously imposed by the national parliament. Although instrumental, expressive, and information-based theories of voter participation imply effects of term limits on turnout, this is clearly an under-researched topic. Applying a difference-in-differences approach to data at both the municipal and parish levels, we find robust evidence that the presence of term-limited incumbents has a positive impact on voter participation.